The coronial manual and the bureaucratic logic of the coroner's office. Issue 2 (22nd June 2016) - Trabsky, Marc
Abstract: This paper examines the coronial manual as a technique of occupying office in the nineteenth and twentieth centuries. The manual guided coroners in the performance of their duties, obligations and responsibilities. It was preoccupied with questions of technical knowledge, operational processes and administrative procedure. The language of office that characterised coronial treatises prior to the eighteenth century was gradually supplemented in the nineteenth century by the discourse of bureaucracy. This paper argues that the guidebook professionalised the office of coroner in Australia by setting out procedures, forms and rituals for assuming responsibility for the dead. It also provided advice to coroners for devoting themselves to a vocation in the public service. The paper thus traces historical shifts in the technology of the coronial manual in British colonies and examines how a bureaucratic logic of the coroner's office affected the way in which coroners pursued justice during the death investigation process.